Dermatological conditions associated with HIV medication in a cohort of Greek patients initiating antiretroviral therapy: 1988-2013 - I.l.i.a.n.a. Alexoudi; A.l.e.x.a.n.d.r.a. Katsarou; V.a.s.s.i.l.e.i.o.s. Paparizos; K.o.n.s.t.a.n.t.i.n.o. Oikonomou; S.o.f.i.a. Kourkounti; G.e.o.r.g.i.a. Augerinou; C.h.r.i.s.t.i.n.a. Antoniou (Elsevier, 2018)
Objectives: Treatment of HIV infection has evolved from a single antiretroviral agent to combination therapy, which has dramatically improved both the quality of life and life expectancy of affected patients. The aim of this study was to review HIV treatment-associated dermatological conditions observed in adult patients receiving antiretroviral therapy (ART) in a single tertiary care referral centre over time.Methods: We reviewed the files of HIV-positive patients seen at the Dermatology Department, AIDS Clinic of the Andreas Syggros Hospital, Athens, Greece who had initiated ART from 1988 to 2013, for evidence of dermatological conditions commonly associated with HIV-related medication.Results: Among a cohort of 1329 HIV-positive patients (1155 men and 174 women), 352 (299 men and 53 women) presented with at least one dermatological condition, with a total of 423 conditions diagnosed that could be attributed to HIV-related medication. Lipodystrophy (47.42%), and maculopapular (MP) rash (40.6%) were most commonly diagnosed. There were three incidence peaks for these reactions, which reflected the different types of ART and HIV-related drugs commonly used at the time. After 2006, the number of these dermatological conditions declined (15.1% of cases) with the availability of newer ART regimens.Conclusions: Early ART was accompanied with a high incidence of adverse skin reactions, which have decreased over time in association with overall better tolerated treatment regimens for HIV infection